Optimizing the Potential of Dampar Beach through Tourism Development, Digitalization, and MSME Empowerment in Dampar Hamlet, Bades Village, Lumajang Regency - Fifin Alfiatur Rohmah; Nur Khasanah; Abdur Ro'uf; Emmy Ermawati (TGO Journal of Community Development, 2026)
Bades Village in Pasirian District, Lumajang Regency, holds significant economic development potential driven by tourism, Micro, Small, and Medium Enterprises (MSMEs), and digital technology advancements. Dampar Beach, noted for its natural beauty, was a key focus of the Student Community Service (KKN) program, as it offers great potential for further tourism development. However, realizing this potential faces several obstacles, including a lack of information about the site, inadequate management of information facilities, digital marketing challenges, unclear business legality, bookkeeping difficulties, and suboptimal use of digital payment systems. The KKN activities involved observation, mapping of existing potential and issues, mentoring, program implementation, supervision, and evaluation. Tourism-related initiatives included aligning the Dampar Beach location on Google Maps, launching the "Explore Dampar" campaign, updating maps and signage, and providing digital resources for tourists and local entrepreneurs. MSME-focused activities included guidance on online marketing and food delivery services, logo and packaging redesign, assistance with obtaining NIB (Business Identification Number) and Halal/P-IRT certifications, setting up digital cashbooks, integrating QRIS payments, and organizing an MSME bazaar. Meanwhile, digital initiatives focused on website creation and improving the village's social media presence. The program results demonstrated improvements in tourism information availability, MSME marketing, business legality, business digitalization, and village information channels. These initiatives can serve as a blueprint for the sustainable development of Dampar Beach and local MSMEs.